CopySwitch—in vivo Optimization of Gene Copy Numbers for Heterologous Gene Expression in Bacillus subtilis - Nadler, Florian; Bracharz, Felix; Kabisch, Johannes (Frontiers in Bioengineering and Biotechnology, 2019)
The Gram-positive bacterium Bacillus subtilis has long been used as a host for production and secretion of industrially relevant enzymes like amylases and proteases. It is imperative for optimal efficiency, to balance protein yield and correct folding. While there are numerous ways of doing so on protein or mRNA level, our approach aims for the underlying number of coding sequences. Gene copy numbers are an important tuning valve for the optimization of heterologous gene expression. While some genes are best expressed from many gene copies, for other genes, medium or even single copy numbers are the only way to avoid formation of inclusion bodies, toxic gene dosage effects or achieve desired levels for metabolic engineering. In order to provide a simple and robust method to address above-mentioned issues in the Gram-positive bacterium Bacillus subtilis, we have developed an automatable system for the tuning of heterologous gene expression based on the host’s intrinsic natural competence and homologous recombination capabilities. Strains are transformed with a linearized, low copy number plasmid containing an antibiotic resistance marker and homology regions up- and downstream of the gene of interest. Said gene is copied onto the vector, rendering it circular and replicative and thus selectable. We could show an up to 3.6-fold higher gfp (green fluorescent protein) expression and up to 1.3-fold higher mPLC (mature phospholipase C) expression after successful transformation. Furthermore, the plasmid-borne gfp expression seems to be more stable, since over the whole cultivation period the share of fluorescent cells compared to all measured cells is consistently higher. A major benefit of this method is the ability to work with very large regions of interest, since all relevant steps are carried out in vivo and are thus far less prone to mechanical DNA damage.